A Systematic Review of Robotic Automated Vegetable Picking Hand - Sukhmeet Singh, Paras Chawla (International Journal of Advanced Science and Technology, 2020)
When the robot word comes in the mind it reflects the term i.e. automatic procedure. The automaticword means robot or machine having a capability of starting, operating, moving etc. independently.There are three methods for moving an object from one place to another i.e. pushing, pulling andpicking. Many researchers have been doing the research on picking an object. The main purpose of thispaper is to find the gaps from the systematic review on picking the vegetable. This systematic review onpicking vegetable was conducted according to PRISMA guidelines. For evidence acquisition wesearched IEEE, Google Scholar and Science Direct libraries. The last search was performed on April05, 2020 by us. We identified 25430 publications from trial search, out of which 16 publications wereretrieved. Out of these 16 publications, 06 publications were excluded due to duplicate publications.Now out of 10 publications only 05 publications are on picking vegetable while other five are onpicking fruits. Thus only 05 publications are of our interest.